Os custos e os lucros em agricultura - Leitão e Silva, Josué (Revista Ceres, 2025)
Costs and returns in agriculture are still under discussion, Farmers are unables to influence the price paid for their production. The author maces a distinction between normal profits and extraordinary profits. On the bases of the actual situation in agriculture, as shown by the data, from his M. S,. thesis, he shows that only 47% of the capital used in milk production received a return of 6% per year.